Caring for a sick or injured child during the COVID‐19 pandemic lockdown in 2020 in the UK: An online survey of parents' experiences. (18th August 2021) - Neill, Sarah; Carter, Rachel; Jones, Ray; Roland, Damian; Bayes, Natasha; Tavaré, Alison; Hughes, Joanne; Turner, Tracy; Chynoweth, Jade; Tan, Chantal; Moll, Henriette; Lakhanpaul, Monica
Abstract: Background: During the COVID‐19 pandemic, the first UK lockdown (March to May 2020) witnessed a dramatic reduction in children presenting to primary/emergency care, creating concern that fear of the virus was resulting in children presenting late. Methods: An online survey was co‐developed with UK parents to understand the impact of the lockdown on parents' help‐seeking for, and care of, their sick/injured child(ren). The survey was advertised through social media and snowballing to parents whose children had been ill/injured during the lockdown. Analysis used descriptive statistics, SPSSv25 and thematic analysis. Results: The survey was fully completed by 198 UK parents. The majority asked for help (144/198): from their family doctor (78), national helplines (48) or an Emergency Department (23). Most reported that their decision‐making had not changed, although how they sought help had changed. A few parents reported that the severity and duration of illness had increased because of uncertainty about and/or difficulty accessing services. Parents did not always report seeking help for symptoms rated red or amber by the Royal College of Paediatrics and Child Health. Parents reported accessing information through the internet or using information that they already had. Parent Contribution: This was a collaboration with parents from survey development to dissemination, with two parents being integral members of our research team. Conclusions: Our questionnaire was completed by parents who were not deterred from seeking help for their sick or injured children. Even for these parents, the lockdown changes to services created uncertainty about, and barriers to, accessing medical help for their children.